2011
DOI: 10.1186/1556-276x-6-195
|View full text |Cite
|
Sign up to set email alerts
|

Promotion of allergic immune responses by intranasally-administrated nanosilica particles in mice

Abstract: With the increase in use of nanomaterials, there is growing concern regarding their potential health risks. However, few studies have assessed the role of the different physical characteristics of nanomaterials in allergic responses. Here, we examined whether intranasally administered silica particles of various sizes have the capacity to promote allergic immune responses in mice. We used nanosilica particles with diameters of 30 or 70 nm (nSP30 or nSP70, respectively), and conventional micro-sized silica part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
2
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 20 publications
1
53
2
1
Order By: Relevance
“…Guichard et al (2015) reported cytotoxic and genotoxic effects in V79 cells exposed to 20-nm size amorphous silica that had been pre-dispersed in bovine serum albumin-water medium. Induction of allergen-specific T H 2-type allergic immune responses to nano-silica was reported by Yoshida et al (2011). Fruijtier-Pölloth (2012 reported on the adverse effects of synthetic amorphous silica on human lung epithelial cell membrane structure and integrity.…”
Section: Discussionmentioning
confidence: 99%
“…Guichard et al (2015) reported cytotoxic and genotoxic effects in V79 cells exposed to 20-nm size amorphous silica that had been pre-dispersed in bovine serum albumin-water medium. Induction of allergen-specific T H 2-type allergic immune responses to nano-silica was reported by Yoshida et al (2011). Fruijtier-Pölloth (2012 reported on the adverse effects of synthetic amorphous silica on human lung epithelial cell membrane structure and integrity.…”
Section: Discussionmentioning
confidence: 99%
“…-approve the new edition of the Regulation on SHM in view of the Federal Law dated June, 29 th , 2016 No. 277-FZ "On Amendments to the Federal Law "On protection of rights of legal entities and individual entrepreneurs in the exercise of state control (surveillance) and municipal control" and the Federal law "On the strategic planning in the Russian Federation".…”
Section: Cross-spectrum Analysis Of Shm Observation Results and Contrmentioning
confidence: 99%
“…Everywhere SHM data are used for the integrated hygienic assessment of the regions [1,4,6,11,19]. Publications by the experts from Sverdlovsk, Kaliningrad, Voronezh and Lipetsk regions, the Republic of Tatarstan, a number of other regions show that the information on negative effects of environment quality towards population health are the basis for the regional action-plans in the field of sanitary and epidemiological welfare of the population [22,26,28,29]. In St. Petersburg, Moscow, Irkutsk regions, SHM results were used in urban development and spatial planning [3,10,13].…”
Section: Issues Per Yearmentioning
confidence: 99%
“…Otros estudios indican que las NP de sílice pueden favorecer respuestas inmunes alérgicas de tipo Th2 en ratones expuestos a OVA, induciendo mayores niveles de inmunoglobulinas IgE, IgG e IgG1 (47). Estas NP también inducen la producción de TNF-a dependiente de la producción de ROS y de la activación de las proteínas cinasas activadas por mitógenos (MAPK, por la sigla en inglés de mitogen-activated protein kinases) en macrófagos, activando una respuesta inflamatoria (48,49).…”
Section: Nanopartículas De Síliceunclassified